THE ROLE OF VISUAL COMMUNICATION AS TOURISM IDENTITY - Utoyo, Arsa Widitiarsa (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Tarumanagara, 2022)
This brief study aims to acquaint the reader with a promising but underutilized scientific inquiry tool in tourism research, namely visual communication analysis. What is the identity of the tourist spot? The role of visual communication in tourist attractions? While the use of visual communication analysis employed by tourism researchers is not new, particularly in terms of tourism representation, the full potential of this research method can still be better utilized. The method used is a qualitative analysis where the data sources used are from books, previous journals to the website, the data that has been collected are then analyzed using the literature method. Interesting design artworks will be seen and even responded to by the audience because creating a work of art is strongly influenced by emotions so that connoisseurs of the work will be moved and the message implied in the design can reach their brains, so that it can boost sales or promotion of goods or services advertised. In designing a visual identity there should be a lot of previous studies and observations about the design field to be worked on. This study provides a brief overview of tourism representations and the literature on visual communication, underlines the importance of this question, and poses a few research questions worthy of future consideration.